ACCOUNTING FOR EMERGENCY RELIEF FUNDS. - Preu, F. L.; Schoen, J. F. (The Accounting Review, 1940)
Abstract Accounting by departments of the Federal Government is not often referred to as a model of modern efficiency, and is commonly regarded as dating from the Hamiltonian era. The organization under the Commissioner of Accounts and Deposits of the United States Treasury Department which performs the accounting functions with respect to funds appropriated by the United States Congress for Emergency Relief, however, has demonstrated that it is possible to maintain an accounting system in the Government which is comparable to systems of the largest and most progressive industrial corporations. Expenditures made under the Emergency Relief Appropriation Acts amounted to $11,924,829,853 as of January 31, 1940 and the tremendous job required for detailed accounting and reporting in connection with these disbursements was accomplished with speed, accuracy and efficiency having infinite lessons and applications for the whole Federal accounting system. The Federal Government in adopting this system of accounting for Emergency Relief expenditures has demonstrated that it is possible for it to maintain a system of accounting as efficient as private industry.